ANALISIS PERILAKU NIKAH SIRI PASANGAN DIBAWAH UMUR TANPA LEGELITAS HUKUM BERDASARKAN UU No. 16 TAHUN 2019 PASAL 7 AYAT 1 TENTANG BATAS USIA PERNIKAHAN - Mohammad Faizin; Sutriyono; Nur Halima (An Nafi': Multidisciplinary Science, 2025)
This research analyzes the behavior of underage unregistered marriages (nikah siri) conducted by couples from the perspective of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage. The main focus of this study lies in Article 7 paragraph (1), which stipulates that the minimum legal age for marriage for both men and women is 19 years. The research method used is library research with a statutory approach. The results show that underage unregistered marriages occur due to several factors, including economic conditions, low levels of education, and attempts to avoid adultery (zina). However, from the perspective of positive law, this practice has no legal validity because the marriage is not registered with the Marriage Registrar (Pegawai Pencatat Nikah/PPN), thereby violating the administrative requirements set by the state. The absence of legal recognition results in the loss of legal protection for the wife and children, including difficulties in obtaining civil rights such as birth certificates and inheritance rights. Although Law Number 16 of 2019 provides a legal mechanism through Marriage Dispensation in the Religious Court, unregistered underage marriages are still considered a form of legal circumvention, as they disregard the protection of children's rights and undermine the long-term objective of family stability mandated by the law.